Perancangan dan Implementasi Sistem Informasi Distributor Sepeda “Dunia Sepeda Pati” Berbasis Web Menggunakan Framework Laravel - Yulius Arif Sugiarto (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
The world of distribution is the world to channel the production carried out by the company. One of the business fields of this distribution is the Dunia Sepeda Kota Pati. The distribution of bicycles in the Dunia Sepeda Kota Pati is still done by manual or conventional recording in a book that has a low level of accuracy, checking that takes a relatively long time, handling data that takes time and paper, and has the potential to lose data. There are five stages of research in this study, namely Needs Analysis and Data Collection, System Design, Application/Program Design, System Implementation and Testing, Testing Analysis Results, and Report Writing. The result of this design is a web-based distributor information system with the Laravel framework which has 5 main menus for super admins, and 4 main menus for admins. This information system can be updated in real-time which includes recording incoming and outgoing goods, number of activities, number of products, reducing the number of stock items directly if there are goods out to customers, and adding stock directly if there are goods coming in from suppliers.